Understanding Turkish water nationalism and its role in the historical hydraulic development of Turkey - Conker, Ahmet (CAMBRIDGE UNIV PRESS, 2018)
Turkey is fully engaged in its hydraulic mission, very extensively and rapidly developing water resources throughout its territory. The extensive hydraulic development attempts conducted by the Turkish government create local, national, inter-state, and transnational contestations among the different interest groups. A great deal of scholarly literature has analyzed the rationale behind Turkey's massive-scale hydraulic development. While some studies link Turkey's hydraulic mission to its energy and food security, others highlight the importance of domestic conflicts, as in the case of the Kurdish issue in the southeast. However, few works examine the relationship between hydraulic development and state- and nation-making processes in the early period of the republic. This paper seeks to analyze the role of hydraulic development in state- and nation-making in the context of Turkey by looking at the institutional documents published by official authorities and speeches made by key politicians. Drawing mainly upon the theory of water nationalism and its related conceptual frameworks, this study argues that hydraulic development has formed one of the important components of the modernization process in Turkey, thereby playing a significant role in its state- and nation-making processes.
Keywords: water nationalism; Turkey; hydraulic development; POWER; ROGUN; DAM; Area Studies; Ethnic Studies; History; Government & Law